Adaptation and Validation of the Self-Compassion Scale for Youth (SCS-Y) in Indonesia - Pratiwi, Alyaa; Hanami, Yuliana (Journal of Educational, Health and Community Psychology, 2024)
This study aims to adapt and examine the psychometric properties of the Self-Compassion Scale for Youth (SCS-Y) for the Indonesian sample. The adaptation process followed International Test Commission (ITC) guidelines, including translation, expert and peer review, cognitive interview, and pre-final Indonesian version. The SCS-Y, developed by Neff et al. (2021), consists of 6 dimensions of self-compassion with 17 items. After item discrimination analysis, 2 items were identified as poor and eliminated, leading to the further analysis of 15 items. The study involved 337 early adolescents aged 11 - 15 years, enrolled in junior high schools in Indonesia. The reliability test (Cronbach's Alpha= .716) showed the scale is reliable. Construct validity was confirmed using Confirmatory Factor Analysis, with all 15 items being significant. The study supports the applicability of the SCS-Y for early adolescents in Indonesia.